Unlocking the potential of graphene for water oxidation using an orbital hybridization strategy. Issue 2 (16th January 2018) - Yao, Yingfang; Xu, Zhe; Cheng, Feng; Li, Wenchao; Cui, Peixin; Xu, Guangzhou; Xu, Sheng; Wang, Peng; Sheng, Guodong; Yan, Yadong; Yu, Zhentao; Yan, Shicheng; et al.
Abstract : Graphene-based electrocatalytic materials are potential low-cost electrocatalysts for the oxygen evolution reaction (OER). Abstract : Graphene-based electrocatalytic materials are potential low-cost electrocatalysts for the oxygen evolution reaction (OER). However, substantial overpotentials above thermodynamic requirements limit their efficiency and stability in OER-related energy conversion and storage technologies. Here, we embedded CrN crystals into graphene and in situ electrochemically oxidized them to construct graphene materials with encapsulated Cr 6+ ions (Cr 6+ @G). These Cr 6+ @G materials exhibit the lowest OER overpotential of 197 mV at 10 mA cm −2 and excellent stability over 200 h at a high current density of about 120 mA cm −2 in an alkaline electrolyte. Spectroscopic and computational studies confirm a stable ion coordination environment significantly benefiting the downshift of the graphene Fermi level via hybridization of C p orbitals with d orbitals of Cr 6+ ions that enhances the OER activity and stability.